Numerical analyses of stress induced damage during a reciprocating lubricated test of fecmo sps sintered alloy. (September 2017) - Fukumasu, N.K.; Boidi, G.; Seriacopi, V.; Machado, G.A.A.; Souza, R.M.; Machado, I.F.
Abstract: Contact-induced stresses during reciprocating movement may lead to surface/subsurface damage. Sintering processes may be used to produce advanced materials with improved wear and friction behavior, but the volume fraction of pores may compromise structural integrity under high loads or fatigue conditions. In this work, the Finite Element Method (FEM) is applied to analyze contact-induced stress distributions produced by surface and inner pores on boundary lubrication condition during reciprocating tests. Material microstructure and mechanical properties are based on sintered FeCMo produced by Spark Plasma Sintering (SPS) process. Results indicate different behavior of surface pores with the increase of contact pressure. It was also observed that pores close to the surface promote a shift of high stress towards the surface, which may improve pitting resistance. Abstract : Highlights: Finite Element Method applied to analyze a porous material subjected to a reciprocating test. Real pore morphology and distribution included in the numerical domain. Surface pore dynamic behavior is dependent on contact pressure. Pores may be designed to improve surface loading capacity and pitting resistance.